2019
DOI: 10.2147/ijn.s224611
|View full text |Cite
|
Sign up to set email alerts
|

<p>Zein-alpha lipoic acid-loaded nanoparticles to enhance the oral bioavailability of dapoxetine: optimization and clinical pharmacokinetic evaluation</p>

Abstract: BackgroundPremature ejaculation (PE) is the most common type of male sexual disorder with important psychological consequences. Dapoxetine (DPX), a recently approved drug for the treatment of PE, suffers from low bioavailability with large variability that ranges from 15–76% (mean 42%) after oral administration. The objective of this study is to optimize the parameters for the preparation of DPX-Zein-alpha lipoic acid (ALA) nanoparticles (NPs) to improve the bioavailability of DPX and consequently decrease the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…44 The important criteria for efficacy and efficiency of nanoparticles (drug release, biodistribution and cellular uptake) are particle size and size distribution. 46,47 Table 1 shows the PSO-NLCs size variabilities for the prepared formulations. The results revealed that the size ranged from 65.0 to 284.0 nm for formulations F13 and F14, respectively.…”
Section: Results and Discussion Formulation And Optimization Of Pso-nlcsmentioning
confidence: 99%
“…44 The important criteria for efficacy and efficiency of nanoparticles (drug release, biodistribution and cellular uptake) are particle size and size distribution. 46,47 Table 1 shows the PSO-NLCs size variabilities for the prepared formulations. The results revealed that the size ranged from 65.0 to 284.0 nm for formulations F13 and F14, respectively.…”
Section: Results and Discussion Formulation And Optimization Of Pso-nlcsmentioning
confidence: 99%
“…Namely, their use as cryoprotectants endows several advantages such as Maillard browning reactions, particularly detrimental to protein-based nanoformulations, as recently demonstrated for Brij O10-stabilized zein nanoparticles [36]. Moreover, the absence of internal hydrogen bonds enhances the interaction of these cryoprotectants with the carriers, as is true for other nanosystems such as chitosan- [63,64] and zein-based nanoparticles proposed for the oral delivery of dapoxetine and resveratrol [65,66]. In fact, trehalose and sucrose have already demonstrated themselves to be particularly suitable for stabilizing protein-based nanoparticles made up of human serum albumin [67].…”
Section: Freeze-drying Of Protein-based Nanoparticlesmentioning
confidence: 97%
“…They reported an increase in the relative bioavailability by 194% from the prepared formulation when compared to the marketed drug product. 48 In this study, the prepared DPX PNPs formulation is similar to the abovementioned NPs in terms of size and drug load. Our optimized transdermal film loaded with DPX PNPs could be considered as a superior DPX drug delivery system due to avoiding of the drug first-pass effect from the transdermal route.…”
Section: Fluorescence Laser Microscopy Testmentioning
confidence: 99%